Influence of Superplasticators on the Properties of Cement - Askarovich, Askarov Bakhtiyor; Hamidullah's daughter, Sobirova Mukaddas (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses the possibility of increasing the strength of the cement grade by using super plasticizing additives. Revealed and justified the need to reduce the water-cement ratio in order to achieve the best results of strength indicators. We concluded that, when using additives, it helps to reduce the amount of mixing water while maintaining the mobility of the mixture, which subsequently allows increasing the strength.